Molecular basis of learning and memory - Pazarcı, Perçin (Scientific Reports in Medicine, 2024)
As commonly known, learning is the process of acquiring a new information and memory is preservation of acquired information for later use. The difference in learning and memory capacities between different species and between different individuals of same species directed scientists to research the causes of this. According to commonly accepted approach these differences are due to the distinctions in synaptic alterations. In collaboration with advancing molecular techniques, the formation mechanisms of synaptic alterations, the reasons of differences between them, the changes that occur in neurons during learning and the changes that occur in neurons as a result of memory became popular research subjects nowadays. The researches that has been done are insufficient, however, many important findings are obtained until now. The changes that occur in pre-synaptic and post-synaptic neurons during simple non-associative learning, associative learning, short term memory and long term memory have been researched and different molecular mechanisms have been suggested.